2004
DOI: 10.1021/es0493796
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Hyperaccumulation of Nickel, Manganese, and Calcium in Alyssum Leaf Trichomes

Abstract: We have developed commercially viable phytoremediation/phytomining technologies employing Alyssum Ni-hyperaccumulator species to quantitatively extract Ni from soils. The majority of Ni is stored either in Alyssum leaf epidermal cell vacuoles or in the basal portions only of the numerous stellate trichomes. Here, we report simultaneous and region-specific localization of high levels of Ni, Mn, and Ca within Alyssum trichomes as determined by scanning electron microscopy/energy-dispersive X-ray analysis (SEM/ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 19 publications
6
93
1
3
Order By: Relevance
“…Many studies have identified trichomes as sites of metal accumulation, with Broadhurst et al (2004), for example, reporting high levels of Ni, Mn, and Ca in trichomes of A. murale. Despite a marked difference in trichome morphology, sunflower NGTs accumulated Mn and Ca when grown at 100 mM Mn in solution (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified trichomes as sites of metal accumulation, with Broadhurst et al (2004), for example, reporting high levels of Ni, Mn, and Ca in trichomes of A. murale. Despite a marked difference in trichome morphology, sunflower NGTs accumulated Mn and Ca when grown at 100 mM Mn in solution (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation in nonglandular trichomes of several hyperaccumulating plants, including Arabidopsis halleri (Küpper et al 2000;Sarret et al 2000;Zhao et al 2000), Alyssum sp. (Broadhurst et al 2004), and non-hyperaccumulating plants, including Brassica juncea (Salt et al 1995), Arabidopsis thaliana (Ager et al 2003;Domínguez-Solís et al 2004), pumpkin (Cucurbita moschata, Iwasaki and Matsumura 1999), and waterlily (Nymphaea sp., Lavid et al 2001), has been reported. However, the mechanism of metal accumulation and excretion of metals in these structures and their exudates are still under investigation.…”
mentioning
confidence: 99%
“…In a study of four forest species that are Mn hyperaccumulators -Gossia bidwillii, Virotia neurophylla, Macadamia integrifolia and Macadamia tetraphylla -Fernando et al (2006a,b) suggested that the accumulation of the excess Mn in the leaves occurs by storage in the nutrient in the mesophyll cells of the palisade parenchyma (photosynthetically active tissue), as a behavior pattern in these accumulator plants, unlike what occurs with Cu and Ni, which are accumulated in the tissues of the epidermis (trichomas) and in the vacuole (Arru et al, 2004;Broadhurst et al, 2004), and with Zn and Cd, which are accumulated in the vacuoles of the spongy mesophyll cells and apoplast (Küpper et al, 1999;Di Toppi et al, 2005). The accumulation of Mn in the form of oxalate crystals is debatable (González & Lynch, 1999).…”
Section: Resultsmentioning
confidence: 99%